Positions of Chinese Car Manufacturers in the World Car Market - Shuba Olena А.; Han Rui (Bìznes Inform, 2023)
The global car market is one of the most competitive markets in the world, with characteristics including technological advancements, product diversity, competition, and innovation. The aim of the article is to study the experience and features of participation of car manufacturers of the People’s Republic of China (PRC) in the world car market. It is determined that the leading car manufacturers in the world market are China, the USA, Japan, India, and Germany. The leading exporters of cars, in terms of value, are Germany, Japan, the USA, South Korea, and Mexico, in terms of quantity – Japan, Germany, China, South Korea and the USA. It is specified that the contemporary automotive industry of the People’s Republic of China consists of a small number of large companies, most of which have a State-owned share, and thousands of small enterprises that produce auto components and spare parts for local companies. The competitive advantage of Chinese cars, which increases their exports, remains their cost. The results of the carried out trend analysis indicate that the growth of exports of cars produced in China will continue in the coming years. It is examined how the PRC government stimulated car manufacturers to achieve leadership in the production of electric vehicles. That is, electric bus lines were laid in several cities of the country and electric vehicles were purchased, all of them made in China. It was the introduction of electric public transport and taxi fleets that helped Chinese car manufacturers subsequently become leaders in the global electric transport market. In the field of production of environmentally friendly cars, the leader is BYD company, being the largest manufacturer of electric vehicles in the world. The following features of the participation of automobile companies of the People’s Republic of China in the world car market are specified: export of a wide range of cars (from the least expensive to premium), the quantitative output of which is larger than in any country in the world; the People’s Republic of China not only develops its own production, but also expands its presence in the global automotive industry, using acquisitions, joint ventures and strategic partnerships; China is one of the largest markets for potential car consumers in the world, from which global car manufacturers are being gradually squeezed out, who cannot compete with locally produced cars in terms of price and range; it is projected that the average annual growth rate in the automotive industry of the People’s Republic of China in the coming years will reach 4.0%. It is concluded that China’s car manufacturers are active participants in the global car market and leaders in the export of new cars, including electric vehicles, the quality and safety of which have significantly improved in recent years.